Pengaruh Media Sosial Marketing Terhadap Keputusan Pembelian pada Produk Skintific 5X Ceramide Low pH Cleanser - Suci Riskiawati; Muhammad Naufal Somantri; Dian Clara Cantika Verina; Helin G Yudawisastra (Indo Publishing, 2026)
This study aims to analyze the effect of social media marketing on purchasing decisions for Skintific 5X Ceramide Low pH Cleanser products. The development of social media has encouraged skincare companies to utilize digital platforms as effective marketing tools to influence consumer behavior. This study uses a quantitative approach with a survey method. The research subjects were users of Skintific 5X Ceramide Low pH Cleanser who learned about the product through social media. There were 60 respondents in this study, selected using purposive sampling. Data were collected through questionnaires and analyzed using descriptive and verifiable analysis. The results show that social media marketing has a positive impact on the purchase decision of Skintific 5X Ceramide Low pH Cleanser. These findings support signal theory, which states that information conveyed through social media serves as a signal of product quality that can increase consumer trust and influence purchasing decisions. This study is expected to contribute to companies in designing social media marketing strategies and serve as a reference for further research.